2017
DOI: 10.1177/1043463117734171
|View full text |Cite
|
Sign up to set email alerts
|

Boosting trust by facilitating communication: A model of trustee investments in information sharing

Abstract: Trust problems hamper many social and economic exchanges. In such situations, there are often institutions that enable trustors to share information on the performance of trustees. While the benefits of such institutions have been researched extensively, little is known about their emergence. This article presents a gametheoretic model for the understanding of investments by trustees in establishing information sharing between trustors. The model allows for a simultaneous analysis of investments in and effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…Kreps et al (1982) have shown how to derive conditions for cooperation in finitely repeated games and for learning about unobservable characteristics of the partner in such games. Using an approach analogous to Frey et al (2015) and Frey (2017), one could derive conditions for strategic tie formation and subsequent cooperation for a finitely repeated PD as well as a finitely repeated Trust Game (see Przepiorka and Diekmann, 2013, for a somewhat similar model, including experimental work, for Trust Games with incomplete information). Note that this includes analyzing learning about unobservable characteristics of the partner not only in the finitely repeated PD or in the finitely repeated Trust Game.…”
Section: Some Extensionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kreps et al (1982) have shown how to derive conditions for cooperation in finitely repeated games and for learning about unobservable characteristics of the partner in such games. Using an approach analogous to Frey et al (2015) and Frey (2017), one could derive conditions for strategic tie formation and subsequent cooperation for a finitely repeated PD as well as a finitely repeated Trust Game (see Przepiorka and Diekmann, 2013, for a somewhat similar model, including experimental work, for Trust Games with incomplete information). Note that this includes analyzing learning about unobservable characteristics of the partner not only in the finitely repeated PD or in the finitely repeated Trust Game.…”
Section: Some Extensionsmentioning
confidence: 99%
“…Assuming a finitely repeated game with incomplete information, investments in strategic tie formation still serve commitment purposes in the sense of making an actor voluntarily vulnerable to future sanctions of the partner (the “binding effect” of commitments, see Raub, 2004). In addition, the question arises (see Frey, 2017, for how to approach the issue in the context of strategic network formation) whether investments in strategic tie formation likewise allow for inferences about unobservable characteristics of the actor who is willing to invest in strategic tie formation (the “signaling effect” of commitment, see Raub, 2004).…”
Section: Analysis Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study contributes to the literatures on strategic information sharing and the role of exchange barriers and costs for the functioning of reputation mechanisms (Brown and Zehnder 2010;Frey 2017;Gërxhani et al 2013;Abraham et al 2016). We consider the effects of voluntary information sharing and of exchange barriers on both trustors and trustees.…”
Section: Introductionmentioning
confidence: 98%
“…The automatic provision of feedback, for example, in online markets or through third party institutions such as credit bureaus and consumer protection agencies, can facilitate information exchange and help overcome barriers to information sharing among market participants. In other cases, the sharing of information does not occur automatically, but requires the strategic decisions of actors who weigh the benefits of information sharing against its costs (Pagano and Jappelli 1993 ; Frey 2017 ). This creates a second - order social dilemma (Fehr and Gächter 2002 ; Ostrom 1990 ) in which individuals may decide not to share their experiences, even though the transfer of information helps to establish market transparency, to bridge information asymmetries, and to overcome trust and moral hazard problems.…”
Section: Introductionmentioning
confidence: 99%